The lived experience of weight loss maintenance in young people - Nicola Sides; Andy Pringle; Lisa Newson (Health Expectations)
Abstract Introduction There continues to be an imbalance of research into weight loss and weight loss maintenance (WLM), with a particular lack of research into WLM in young people under 18 years. Failure to coherently understand WLM in young people may be a potential contributor to the underdeveloped guidance surrounding long‐term support. Furthermore, no research has investigated young people's preferences around WLM support following the attendance of a residential intensive weight loss intervention from a qualitative perspective. This study explored the influences of WLM in young people following a residential intensive weight loss intervention, considered how interventions could be improved and sought to develop recommendations for stakeholders responsible for designing WLM interventions. Methods The context in which this research is framed was taken from a residential Intensive Weight Loss Intervention for young people aged 8–17 years in England. Six semi‐structured interviews were carried out to understand the lived experience of WLM, including barriers and enablers influencing WLM, adopting an interpretative phenomenological analysis design. Findings Three superordinate themes were developed to explain the barriers and enablers to WLM; (1) Behavioural control and the psychosocial skills to self‐regulate WLM; (2) Delivering effective social support; and (3) Conflicting priorities and environmental triggers. Conclusion The findings of this research mirror that of other studies of WLM in young people, with the majority of young people struggling to maintain weight loss. However, by exploring the experience of WLM in young people through qualitative means, it was possible to understand the specific motivators and barriers influencing WLM behaviours in this context, providing recommendations to support WLM. Patient or Public Contribution The interview guide was developed in consultation with a young person from the intervention, and through discussions with the intervention stakeholders (delivery staff and management staff). The interview guide included topics such as knowledge and skills; experience of weight loss; reflections on weight maintenance, and experiences of daily life postintervention. We piloted the interview schedule with one young person who had consented to take part in the research. This first interview was used to check for understanding of questions and to assess the flow of the interview.